The New Ways In The Distance Education - MAZILU, Mirela (Journal of Research in Educational Sciences; Vol 1 No 1 (2010): JRES Volume I Issue 1(1) Summer 2010, 2010)
The new ways of learning available in the distance education programs differ a lot from the traditional ones. That is the reason why the more and more ample integration of the new informatics and communication technologies in the learning process, needs a profound reconsidering of the contemporary didactics, because the new means of learning available through these new technologies differ fundamentally from the learning and the teaching of the traditional classroom. This reconsideration must start firstly from the analysis of the features of these new technologies, and of the multiple functions which they can fulfil: the communicating functions, the demonstration, the solution of the problems, the research, the simulation, the assessment, and even the sensitivity and the increase in motivation. Otherwise, these programs risk to having a smaller effect than the one expected.